Physiological Regulation of Growth, Hematology and Blood Gases in Chicken Embryos in Response to Low and High Incubation Humidity - Branum, Sylvia; Tazawa, Hiroshi; Burggren, Warren (Frontiers in Physiology, 2022)
Variations from a relative humidity (RH) of ~50-60% can unfavorably alter chicken embryo development, but little is known of whether the embryo can mitigate these effects through physiological regulation. We examined effects of Low RH (25-35%), and High RH (85-93%) compared to Control RH (50-60%) on hatchability, embryonic growth, hematology and blood gases and pH. Mean hatchability was not affected by RH. Yet, Low RH decreased wet body mass of advanced embryos (days 17-19; d17-19), with lowered body water content compared with embryos of Control and High RH. However, dry body mass of developing (d11-19) embryos was not different between the three RH groups. Mean blood osmolality across development was higher in Low RH embryos and lower in High RH embryos compared with Control embryos. Mean blood lactate was higher in both Low and High RH embryos compared to Control embryos. Unexpectedly, hematological respiratory variables (Hct, [RBC], MCV, [Hb]) and blood gas variables (Po2, Pco2, pH, [HCO3-]) across development were not affected by RH. Mean wet body mass at hatch (d20-22) was larger in High RH embryos compared with Low RH embryos, but mean wet and dry body mass upon euthanasia on d22 was unaffected. The ability of the three populations to physiologically regulate blood respiratory variables and blood acid-base balance was then examined by observing their responses to intrinsic hypoxemia and hypercapnia created by controlled partial egg submersion in water. Hct and [RBC] responses were less disturbed by submersion in High RH embryos compared with both Control and Low RH embryos, which showed major disturbance. Acid-base regulatory responses did not differ between RH groups. We conclude that, while different incubation RHs cause large differences in tissue water content and body mass, most hematological and acid-base regulatory capabilities are regulated near Control values.